Critical evaluation of ecosystem changes from an offshore wind farm: producing natural capital asset and risk registers - Causon, Paul D.; Jude, Simon; Gill, Andrew B.; Leinster, Paul (Elsevier, 2022)
Offshore wind infrastructure modifies benthic habitats, affecting ecosystem services. A natural capital approach allows risks to nature-based assets and ecosystem benefits to be assessed. The UK Natural Capital Committee produced guidance for conducting natural capital assessments to aid decision making processes. Development of an asset register and risk register are key components of this methodology. The former provides an inventory of NC stocks, and the latter considers the likelihood of changes and the scale of their impact on delivery of ecosystem services. In this study, suitability of the methodology in a marine environment context was critically evaluated. Natural capital stocks before and after installation of Greater Gabbard offshore wind farm were compared and risks to delivery of ecosystem services were assessed. It was demonstrated that incorporating an assessment of impacts on natural capital assets in planning and management decisions (as an extension to traditional environmental impact assessment approaches) could further facilitate sustainable use of marine ecosystems. For example, by preventing access to bottom-trawl fisheries activities, wind farms may promote recovery and increase value of seabed natural capital assets. By also introducing aquaculture systems loss of food provision (from reduced fishing activity) could be offset whilst allowing benthic natural capital assets to recover. Natural capital assessment is relevant to the marine context. However, application of the Natural Capital Committee’s methodology was constrained by the limited coverage of standard benthic sampling tools. Given the scale of wind energy plans across the marine environment it is recommended that these shortcomings are appropriately addressed.
Keywords: Benthic community; Ecosystem services; Environmental management; Natural capital; Offshore wind farm